Cognition, optimism and the formation of age-dependent survival beliefs - Nils Grevenbrock; Max Groneck; Alexander Ludwig; Alexander Zimper (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
This paper investigates the roles psychological biases play in empirically estimated deviations between subjective survival beliefs (SSBs) and objective survival probabilities (OSPs). We model deviations between SSBs and OSPs through age-dependent inverse S-shaped probability weighting functions (PWFs), as documented in experimental prospect theory. Our estimates suggest that the implied measures for cognitive weakness, likelihood insensitivity, and those for motivational biases, relative pessimism, increase with age. We document that direct measures of cognitive weakness and motivational attitudes share these trends. Our regression analyses confirm that these factors play strong quantitative roles in the formation of subjective survival beliefs. In particular, cognitive weakness is an increasingly important contributor to the overestimation of survival chances in old age.
Keywords: D12; D83; I10; 330; Subjective Survival Beliefs; Probability Weighting Function; Confirmatory Bias; Cognition; Optimism